PENGARUH CLEARANCE DAN PEMBEBANAN RADIAL TERHADAP PERPINDAHAN, DISTRIBUSI BEBAN KONTAK, DAN KEKAKUAN ELEMEN ROL PADA SPHERICAL ROLLER BEARING - Hendery Dahlan; Rahmi Safitri; Meifal Rusli; Mulyadi Bur (Jurnal Rekayasa Mesin, 2023)
This study aims to determine the effect of clearance and loading regarding to the displacement, distribution of contact loads and stiffness of spherical roller bearings at rest. The displacement formulation of the inner ring of the bearing was developed by defining the angle of inclination of the roller element to the axis of shaft. The comparison between exact calculations using the Matlab program and numerical modeling with MSC Marc for the displacement has an error value of less than 10%. Therefore, the displacement formulation of the inner ring of the bearing is used to calculate the exact distribution of contact load and stiffness of the spherical roller bearing and numerical modeling. The results revealed that the effect of clearance and loading on the displacement of the inner ring of the spherical roller bearing is directly proportional. The contact load of the bearing roller element is distributed over the part of the roller element that is in contact with its path, where the largest contact load occurs at the position of the roller element parallel to the axis of the shaft at rest. Meanwhile, bearing stiffness will decreases with increasing the value of clearance.